Assessing the ecological status of an estuarine ecosystem: linking biodiversity and food-web indicators. (15th November 2019) - Le Guen, Camille; Tecchio, Samuele; Dauvin, Jean-Claude; De Roton, Gwenola; Lobry, Jérémy; Lepage, Mario; Morin, Jocelyne; Lassalle, Géraldine; Raoux, Aurore; Niquil, Nathalie
Abstract: During the last decades, the highly-anthropized Seine estuary has been impacted by modification of its habitats (building of a major extension of Le Havre harbour, i.e. Port2000) and a significant natural decrease in freshwater discharge. A Before/After analysis, using a toolbox of indicators, was applied to characterize the effects of both events on the estuarine ecosystem status. We selected from existing tool boxes several indicators derived from food web modelling or community composition data, such as biodiversity indicators, a guild-based index ( i.e. Estuarine and Lagoon Fish Index ELFI) and ecological network analysis (ENA) indices. ENA and biodiversity indicators were applied on six spatial boxes describing the Seine estuary and its outlet. Results showed an increase in taxonomic and functional richness over time, mainly due to marinisation, and significant changes in food-web properties in relation to Port2000. ENA indices appeared as a promising method in ecological status assessment, especially for estuaries considered as inherently disturbed. Graphical abstract: Image 1 Highlights: The Seine estuary ecosystem was described before and after the Port2000 extension. A toolbox of various indices was used, describing complementary characteristics. Port2000 effects were complex to separate from other human-induced and natural effects. Ecological Network Analysis was useful in defining functional indicators. The need to continue long-term monitoring and to use multiple tools is emphasized.